2012
DOI: 10.1098/rspa.2012.0193
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of an actuated seafloor-mounted carpet for a high-performance wave energy extraction

Abstract: It is known that muddy seafloors can extract significant energy from overpassing surface waves via engaging them in strong interaction processes. If a synthetic seabed can respond to the action of surface gravity waves similar to the mud response, then it too can take out a lot of energy from surface waves. Analysis of the performance of a mud-resembling seabed carpet in harvesting ocean wave energy is the subject of this article. Specifically, and on the basis of the field measurements and observations of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 24 publications
2
43
0
1
Order By: Relevance
“…At early stages of device development, numerical models can allow rapid estimates of the energy capture performance of a device (Pizer, 1992;Josset et al, 2007;Payne et al, 2008;Kurniawan et al, 2011;Babarit et al, 2012), and provide powerful tools to gain insight in the behaviour of novel device configurations (Renzi and Dias, 2012;Alam, 2012;Farley et al, 2011;Lovas et al, 2010). The use of efficient numerical models allows extended parametric studies and optimization to be performed more rapidly than can be achieved experimentally (Malmo and Reitan, 1985;Babarit et al, 2005;Folley et al, 2007a,b;Vicente et al, 2009;Gomes et al, 2011;Oskamp and Ozkan-Haller, 2012;Falcao et al, 2012).…”
Section: Numerical Modelling Of Wave Energy Convertersmentioning
confidence: 97%
“…At early stages of device development, numerical models can allow rapid estimates of the energy capture performance of a device (Pizer, 1992;Josset et al, 2007;Payne et al, 2008;Kurniawan et al, 2011;Babarit et al, 2012), and provide powerful tools to gain insight in the behaviour of novel device configurations (Renzi and Dias, 2012;Alam, 2012;Farley et al, 2011;Lovas et al, 2010). The use of efficient numerical models allows extended parametric studies and optimization to be performed more rapidly than can be achieved experimentally (Malmo and Reitan, 1985;Babarit et al, 2005;Folley et al, 2007a,b;Vicente et al, 2009;Gomes et al, 2011;Oskamp and Ozkan-Haller, 2012;Falcao et al, 2012).…”
Section: Numerical Modelling Of Wave Energy Convertersmentioning
confidence: 97%
“…Under simplifying assumptions of an infinitely long, twodimensional and linear visco-elastic carpet with uniformly distributed actuation under the action of the overpassing waves (assuming inviscid and irrotational flow), we showed that [12,13] the linearized form of the governing equations admits two modes of motion: a surface-mode and a bottom-mode. While damping of surface-mode waves is higher for longer waves, the damping of a bottom-mode wave is higher for shorter waves.…”
Section: Wave Carpet: a Broadband And Omnidirectional Wave Energy Conmentioning
confidence: 99%
“…We have investigated mud theoretically and computationally in the linear and weakly nonlinear regimes [12,13], and experimentally with the purpose of providing a proof of the concept [14]. Under simplifying assumptions of an infinitely long, twodimensional and linear visco-elastic carpet with uniformly distributed actuation under the action of the overpassing waves (assuming inviscid and irrotational flow), we showed that [12,13] the linearized form of the governing equations admits two modes of motion: a surface-mode and a bottom-mode.…”
Section: Wave Carpet: a Broadband And Omnidirectional Wave Energy Conmentioning
confidence: 99%
See 2 more Smart Citations